(untitled) (Research, Society and Development, 2022)
To assess whether there is an association between pain and anxiety in children during dental treatment. This is a longitudinal observational study, in which pain and anxiety were evaluated in 18 children aged 6 to 10 years attended in two dental consultations at the Pediatric Dentistry clinic of UNIFAL-MG. Before each consultation, the presence of pain was evaluated using the Wong Baker FACES Scale (WBFS) and anxiety using the Facial Image Scale (FIS) and the Modified Come Picture Test (VTP-M). Data were analyzed using the Mann-Whitney and Spearman test (P<0.05; IBM-SPSS, version 25.0). There was a statistically significant correlation between pain and anxiety using the FIS scale (P<0.01; rho=0.81; P=0.004; rho=0.64) in the first and second consultations, respectively. However, there was no correlation between both variables using the VTP-M scale for the first and second consultations, respectively (P=0.08; rho=0.36; P=0.05; rho=0.46). Regarding the type of treatment, there was an association with pain in both consultations and with anxiety (FIS) only in the second consultation (P<0.05). Children with greater pain complaints had a greater degree of anxiety during dental appointments. Therefore, the presence of pain may be one of the factors responsible for causing childhood anxiety, in addition to being exacerbated by the type of dental treatment.